Record keeping in psychotherapy and counseling : protecting confidentiality and the professional relationship - Luepker, Ellen T. (New York, NY : Routledge, 2012)
'As in the first edition, Record Keeping in Psychotherapy and Counseling provides a general, supportive framework for understanding the reasons surrounding confidentiality and privacy parameters. It clarifies dilemmas and strategies surrounding these issues in order to help professionals protect themselves and their clients, patients, students, and supervisees. To bring the book up-to-date, the author references new books, articles, laws, and court decisions pertaining to record keeping and confidentiality, includes practitioners' experiences implementing the Health Insurance Portability and Accountability Act (which was enacted just after the first edition was published), and adds a completely new chapter on electronic records. New illustrations and case examples are employed to keep the text fresh and lively, and an accompanying CD contains useful and editable forms'--
Book is accompanied by one computer optical discs entitled'Record keeping in psychotherapy and counseling : protecting confidentiality and the professional relationship' bearing the sama call number and available at Unit Koleksi Media.
Includes bibliographical references (pages 247-255) and index.
Keywords: Psychiatric records